PENDAMPINGAN PERHITUNGAN HARGA POKOK PRODUKSI DAN PENGELOLAAN KEUANGAN GUNA MENINGKATKAN KINERJA KEUANGAN UMKM MUJAMU - Pratiwi, Desy Nur; Pravasanti, Yuwita Ariessa; Meliani, Novita Kinsky (LPPM ITB AAS Indonesia Surakarta, 2024)
This community service (PkM) activity aims to improve the financial performance of Mujamu MSMEs. The problems faced by partners are the difficulty in determining the cost of production so that they sell products based on market prices and do not yet know how to manage finances properly because business finances are still mixed with personal finances. With these problems, the Community Service team provides assistance in calculating the cost of production and financial management to Mujamu MSMEs. The assistance activities were carried out for 8 weeks starting from preparation to compiling reports. The results of the PkM activities showed that Partners experienced an increase in understanding and ability to calculate the cost of production and partners were able to record each transaction and make simple records in order to implement good financial management. Keywords: Cost of Production, Financial Management, Mujamu MSMEs